Ethnopsychological Features of Brides on Adaptation to Family (with the Example of Kazakh and Uzbek Families) - Kurbanovna, Arapbaeva Damegul (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the results of the method of "Socio-psychological adaptation" by K. Rodgers and R. Diamond in the study of the level of socio-psychological adaptation in newlyweds. The coefficients of correlation between the indicators of the process of adaptation of brides to the family are studied on the example of Kazakh and Uzbek families.The problem of social adaptation is an important part of the research that psychology is studying. Because psychological adaptation is seen as a process of establishing adaptation between an individual and a group, society and the environment.In order to study the socio-psychological adaptation of newlyweds to the family, our empirical study is conducted in Kazakh families living in Konimex district of Navoi region, Republic of Uzbekistan. The main object of the study is 50 newlywed Kazakh brides. 50 newlywed Uzbek brides living in Navbahor district will be taken as a control group.It is noted that using this method, it is possible to study the individual and typical aspects of the attitude of brides to themselves, self-acceptance, as well as to understand their problems and try to solve them, as well as to determine the level of socio-psychological flexibility.The process of adaptation is directly important in adapting to a new environment. When interpreting a person’s adaptation to a new environment, the main focus is on the psychological states of the bride’s adaptation to the new family and circumstances. It should be noted that personal and professional relationships with family members, the establishment of moral norms and values of the family create socio-psychological adaptation. The newlyweds become acquainted with family values and social norms as a new member of the family. It is noted that the process of socio-psychological adaptation can be complex and long-term.